Mutu Pelayanan sebagai Mediasi Pengaruh Karakteristik Pasien dan Standar Pelayanan Minimum terhadap Kepuasan Pasien di Puskesmas Bluto - Purnomo Wirawan; Rusdiyanto Rusdiyanto; Chamariyah Chamariyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study explores the influence of patient characteristics and the implementation of Minimum Service Standards (SPM) on patient satisfaction, with the quality of health services as a mediating variable, at the Bluto Health Center, Sumenep Regency. Using an explanatory quantitative approach, data from 44 respondents were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results showed that patient characteristics and SPM had a significant positive effect on the quality of health services, with path coefficients of 0.471 (p = 0.010) and 0.398 (p = 0.017), respectively. However, patient characteristics and SPM did not have a significant direct effect on patient satisfaction, with path coefficients of 0.106 (p = 0.517) and 0.018 (p = 0.907), respectively. In contrast, the quality of health services had a significant positive effect on patient satisfaction (path coefficient 0.757; p = 0.000). Indirectly, patient characteristics (path coefficient 0.356; p = 0.031) and SPM (path coefficient 0.301; p = 0.025) have a significant positive effect on patient satisfaction through the quality of health services. These results emphasize the importance of the quality of health services as a significant mediating factor. Improving the quality of services is the key to optimizing patient satisfaction through the implementation of SPM and adjustments to patient characteristics.